Analysis of Tourism Development in Libya - Alfartas, Khaled Omran (2009)
A destination image is the expression of all objective knowledge, impressions, prejudice,imaginations, and emotional thoughts an individual or group might have of a particular place.The term tourism is a kind of universal remedy for some of the macroeconomic problems, as an engine for social transformation and to produce a favorable image on the global platform guide in an era giving too generous incentives to the industry. This study has provided significant needs of tourism development in Libya. Factors that affect the tourism development has examine in this study. Correlation and regression analysis had been conducted to determine the relationship among variables and tourism development. I have found that variables, accommodation development, Infrastructure development, training and education, attraction and activities, transportation facilities and tourism product are correlated to the tourism development and by regression analysis this relation have been supported.